In the shadow of the Mahatma : Bishop V.S. Azariah and the travails of Christianity in British India - Harper, Susan Billington (Grand Rapids,Mich.: W.B.Eerdmans Pub.Co., 2000)
Reconstructs major events and issues in Bishop Azariahs public life, including a previously unstudied controversy with Gandhi over the issue of conversion and religious freedom in the 1930s. This book presents the only critical study of the public life and legacy of V.S. Azariah (1874-1945), the first Indian bishop of an Anglican diocese and the most successful leader of rural conversion movements to Christianity in modern India. Harper carefully explores Bishop Azariahs work, including his attempts to redress racism and improve social conditions in India, and documentsfor the first time anywherethe previously unknown controversy between Bishop Azariah and the great Mahatma Gandhi.
Local background: secure roots and a spiritual core -- Pan-Asian ecumenism: a vision beyond nations -- Indigenous national base: a nonpolitical missionary -- Bishop in the British Empire: church-state conflict under the Raj -- Bishop in the Indian Church: race an identity formation -- Bishop in Andhra: local transformation through conversion -- Overcoming divisions in Christendom -- Overcoming caste and culture in India -- The conflict with Gandhi and political nationalism.
Includes bibliographical references (pages 367-442) and index.
Keywords: Azariah, Vedanayagam Samuel, -- 1874-1945.; Church of South India. -- Dornakal Diocese -- Biography; Church of South India -- Bishops -- Biography; India, South -- Church history -- 20th century; Biographies